2015
DOI: 10.1016/j.foodres.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Capability of exopolysaccharide-producing Lactobacillus paraplantarum BGCG11 and its non-producing isogenic strain NB1, to counteract the effect of enteropathogens upon the epithelial cell line HT29-MTX

Abstract: 1BGCG11 and its non-producing isogenic strain NB1, to counteract the effect of 2 enteropathogens upon the epithelial cell line HT29-MTX

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
(36 reference statements)
1
26
0
Order By: Relevance
“…In our study, the results of a SEC-MALLS analysis revealed that insertional mutagenesis of the glps_2198 gene, encoding priming glycosyltransferase, led to the absence of the P2 fraction in EPS7, related to low molecular weight EPS-SJ (13,600 Da) present in BGSJ2-83, as well as to an increase in molecular weight of the P1 and its reduced production. According to literature data the gene encoding priming glycosyltransferase is highly evolutionarily conserved ( Jolly and Stingele, 2001 ) and could be located at the beginning of the eps operons, as reported for L. helveticus NCC2745 ( Jolly et al, 2002 ) and L. paraplantarum BGCG11 ( Zivkovic et al, 2015 ), in the middle of the eps clusters, as in Streptococcus thermophilus strains ( Stingele et al, 1996 ; Almiron-Roig et al, 2000 ), L. lactis NIZO B40 ( Kleerebezem et al, 1999 ), and L. delbrueckii subsp. bulgaricus Lfi5 ( Lamothe et al, 2002 ), or in the vicinity of the end of the eps clusters as in the case of L. rhamnosus ( Péant et al, 2005 ) and here in the case of BGSJ2-8.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In our study, the results of a SEC-MALLS analysis revealed that insertional mutagenesis of the glps_2198 gene, encoding priming glycosyltransferase, led to the absence of the P2 fraction in EPS7, related to low molecular weight EPS-SJ (13,600 Da) present in BGSJ2-83, as well as to an increase in molecular weight of the P1 and its reduced production. According to literature data the gene encoding priming glycosyltransferase is highly evolutionarily conserved ( Jolly and Stingele, 2001 ) and could be located at the beginning of the eps operons, as reported for L. helveticus NCC2745 ( Jolly et al, 2002 ) and L. paraplantarum BGCG11 ( Zivkovic et al, 2015 ), in the middle of the eps clusters, as in Streptococcus thermophilus strains ( Stingele et al, 1996 ; Almiron-Roig et al, 2000 ), L. lactis NIZO B40 ( Kleerebezem et al, 1999 ), and L. delbrueckii subsp. bulgaricus Lfi5 ( Lamothe et al, 2002 ), or in the vicinity of the end of the eps clusters as in the case of L. rhamnosus ( Péant et al, 2005 ) and here in the case of BGSJ2-8.…”
Section: Discussionmentioning
confidence: 83%
“…In this study we have shown that EPS-SJ-producing strain BGSJ2-83 exhibits higher adhesion to Caco-2 cells and is more capable of competing for the colonization of the intestinal niche than E. coli strain ATCC25922. Similarly, non-EPS producing derivative of EPS-CG11 (NB1) more efficiently reduced the association of Clostridium difficile or Yersinia enterocolitica than parental BGCG11 strain ( Zivkovic et al, 2015 ). Interestingly, the presence of EPS-CG11-producing strain BGCG11, exhibiting low adhesion to Caco-2 cells, decreased the association of E. coli ATCC25922 to Caco-2 cells, similarly to previously obtained results by Zivkovic et al (2015) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mental conditions, both outside and inside the host (1,3,4), and in the case of pathogens such as Streptococcus pneumoniae, they can have an important association with immune evasion and virulence (5). EPS can have immunomodulatory and protective properties in the host (6)(7)(8)(9) and can affect the composition and function of the gut microbiota (10,11). EPS can also play a crucial role in biofilm formation, adhesion to host cells, and colonization (3,(12)(13)(14)(15).…”
mentioning
confidence: 99%